2019
DOI: 10.1177/0266666919884348
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the characteristics of 3D printing global industry chain and value chain innovation network

Abstract: In this study, we attempted to fill an important gap that literature has yet to investigate: the characteristics of the 3D printing global industry chain and value chain innovation network. The network characteristics analysis is based on patents and the patent data download from the European Patent Office (EPO) database covering the period from January 1, 1989 to December 31, 2017. The concept of the 3D printing global industry chain and value chain network is defined, then the network model is divided by emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The convergence of various production and distribution phases in a way that adds value to the product at each stage by attaining process specialisation and quality improvement is referred to as a value chain. When the innovation process is combined with the value chain, a "innovative industrial chain and value chain model" emerges, allowing creativity to be expressed in three stages: inspiration, conversion, and execution, or idea creation, conversion, and diffusion (Bai et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The convergence of various production and distribution phases in a way that adds value to the product at each stage by attaining process specialisation and quality improvement is referred to as a value chain. When the innovation process is combined with the value chain, a "innovative industrial chain and value chain model" emerges, allowing creativity to be expressed in three stages: inspiration, conversion, and execution, or idea creation, conversion, and diffusion (Bai et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the current COVID-19 pandemic situation, most of the employees were ordered to work from home (WFH). Science and technology's rapid development has allowed people to continuously change their traditional production and lifestyle (Bai et al, 2019). Now, with technology employees can do their jobs at home and communicate with their colleagues online.…”
Section: Innovative Value Chainmentioning
confidence: 99%
“…Additionally, an overwhelming 95% of manufacturing companies believe that the utilization of 3D printing technology offers a substantial competitive edge in the market. The study also indicated that a significant proportion of 3D printing enterprises, specifically 47%, have experienced greater levels of success compared to their performance in preceding years [18]. According to analysts' projections, the 3D printing sector is expected to experience an average growth rate of 24% or reach a market value of 35 billion dollars within the next five years [19].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the characteristics of FDM printed components, scholarly sources have concentrated on the advancement of composite material systems through the incorporation of various fillers into the base polymer and subsequent printing of these composites [18,19]. The utilization of composites in the production of parts has been observed to result in enhanced mechanical, thermal, and electrical properties when compared to printed parts made solely from unreinforced polymers.…”
Section: Introductionmentioning
confidence: 99%